PERAN KEPUASAN KERJA MEMEDIASI PENGARUH STRES KERJA TERHADAP KOMITMEN ORGANISASIONAL - Putu Arie Tria Dewi; I Gede Aryana Mahayasa; I Komang Gede (Fakultas Ekonomi Universitas Warmadewa, 2023)
This research was conducted at the Secretariat of the Badung Regency DPRD. The number of populations and samples in this study was as many as 73 people with saturated sample methods. Data collection using questionnaires is then tested for validity and reliability. The data analysis techniques used are path analysis (path) and sobel test. The results in this study are 1) Work stress has a negative and significant effect on job satisfaction with a correlation value of -0.555 and a significant value of 0.000 < 0.05. 2) Work stress has a negative and significant effect on organizational commitment with a correlation value of – 0.199 and a significant value of 0.004 < 0.05. 3) Job satisfaction has a positive and significant effect on organizational commitment with a correlation value of 0.515 and a significant value of 0.000 < 0.05. 4) Job satisfaction can mediate the relationship between work stress and organizational commitment with the results of calculations obtained thitung (3,097) > ttabel (1,994). The advice in this study is that the division of duties and responsibilities must be based on the abilities that employees have so as not to cause employee work stress.